The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1182/blood-2014-04-568329
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up from a phase 1/2 study of single-agent bortezomib in relapsed systemic AL amyloidosis

Abstract: • Single-agent bortezomib produces durable hematologic responses and promising long-term overall survival in relapsed AL patients.• Once-weekly bortezomib is better tolerated and produces similar responses to twiceweekly bortezomib in relapsed AL patients.CAN2007 was a phase 1/2 study of once-and twice-weekly single-agent bortezomib in relapsed primary systemic amyloid light chain amyloidosis (AL) amyloidosis. Seventy patients were treated, including 18 and 34 patients at the maximum planned doses on the once-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 46 publications
0
38
0
3
Order By: Relevance
“…[17][18][19] The proteasome inhibitor (PI) bortezomib is approved for the treatment of MM and has shown activity in both previously untreated and relapsed/refractory AL amyloidosis (RRAL) patients. 9,10,20 Demonstrating the feasibility and activity of PI therapy, single-agent or combination bortezomib treatment results in unprecedented high hematologic response rates and rapid and durable responses, 9,20,21 and it has been adopted as a front-line therapy for AL amyloidosis. 5,22 However, AL amyloidosis remains a severe condition with a poor prognosis and a median overall survival of approximately 12 months if untreated, 23,24 dropping to 6 months when the heart is affected 25 ; new treatment options are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] The proteasome inhibitor (PI) bortezomib is approved for the treatment of MM and has shown activity in both previously untreated and relapsed/refractory AL amyloidosis (RRAL) patients. 9,10,20 Demonstrating the feasibility and activity of PI therapy, single-agent or combination bortezomib treatment results in unprecedented high hematologic response rates and rapid and durable responses, 9,20,21 and it has been adopted as a front-line therapy for AL amyloidosis. 5,22 However, AL amyloidosis remains a severe condition with a poor prognosis and a median overall survival of approximately 12 months if untreated, 23,24 dropping to 6 months when the heart is affected 25 ; new treatment options are therefore needed.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although there are no currently approved therapies for patients with relapsed or refractory disease, bortezomib, lenalidomide, and pomalidomide, all of which are approved for the treatment of MM, are effective. 5,[7][8][9][10][11][12] Achievement of a hematologic response is required and predictive of an organ response (which can take up to a year), 13 as well as prolonged survival. 14,15 Response criteria were established in 2005 16 and updated in 2012 based on the difference between levels of involved and uninvolved free light chains (dFLC) 17 ; these updated criteria were later validated.…”
Section: Introductionmentioning
confidence: 99%
“…In a broader view, the intrinsic toxicity for plasma cells of immunoglobulin fragments prone to misfolding and aggregation deserves to be explored in other monoclonal immunoglobulin-related diseases including light chain (AL) amyloidosis and LCDD, in which preliminary studies suggest that bortezomib-based therapy has a strong impact on renal and patient outcomes. 44,[60][61][62] Transgenic mouse models could be of invaluable interest to explore this issue. 36 Altogether, the present transgenic mouse model of HCDD accurately recapitulates the early steps of the human pathology and represents a valuable tool to explore the mechanisms that govern toxicity of truncated HCs and the sequential events leading to glomerular injury in MIDD.…”
Section: Discussionmentioning
confidence: 99%
“…65 Prospective trials and large retrospective series proved the efficacy and tolerability of bortezomib in AL amyloidosis. 66,67 More recently, 2 retrospective series showed unprecedented hematologic response rates (up to 90%, with 60%-65% CRs) in treatment-naive patients receiving CyBorD. 68,69 Subsequently, 2 retrospective matched case-control studies confirmed higher response rates with regimens combining bortezomib, dexamethasone, and alkylating agents (BMDex and CyBorD) compared with standard MDex or cyclophosphamide/ thalidomide/dexamethasone (CTD), but failed to demonstrate an overall survival advantage.…”
Section: What's New In Amyloidosis 163mentioning
confidence: 99%